THE INFLUENCE OF EFFECTIVENESS, TRANSACTION SPEED, AND ACCURACY ON INTENTION TO USE THE INDONESIAN STANDARD QUICK RESPONSE CODE AS A DIGITAL PAYMENT SYSTEM FOR MSMES IN MARITENGNGAE DISTRICT - Eggi Padilla; Romy Nugraha JS; Ari Ayu (Universitas Ichsan Sidenreng Rappang, 2025)
This study aims to determine the effect of effectiveness (X1), transaction speed (X2), and accuracy (X3) partially or simultaneously on the interest in using the Indonesian Standard Quick Response Code (QRIS) among Micro, Small, and Medium Enterprises (MSMEs) in the food and beverage sector in Maritengngae District, Sidenreng Rappang Regency. This study uses a quantitative approach. The number of MSMEs in the food and beverage sector registered in Maritengngae District, Sidenreng Rappang Regency is 1,167 MSMEs (Data on the number of businesses from the Office of Cooperatives, SMEs, Manpower and Transmigration of Sidenreng Rappang Regency, 2023). The sample in this study was MSMEs engaged in the food and beverage sector that have a standard Indonesian quick response code (QRIS) in Maritengngae District, amounting to 70 respondents. The results of the study indicate that partially, effectiveness (X1) has a positive and significant effect on the interest in using QRIS. Transaction speed (X2) also showed a positive and significant influence on interest in using QRIS. However, accuracy (X3) did not have a positive and significant influence on interest in using QRIS. Simultaneously, the three independent variables significantly influenced the dependent variable, namely interest in using QRIS, with a coefficient of determination (R²) of 51.5%. This indicates that 51.5% of the variation in interest in using QRIS can be explained by these three variables, while the remaining 48.5% is influenced by other factors outside the studied variables. This study contributes to understanding the factors influencing QRIS adoption by MSMEs and can serve as a reference in developing policies to promote digitalization of financial transactions in the small business sector.